Association of spiral filamentous viruslike particles with rice hoja blanca - Morales, Francisco José; Niessen, AI (Scientific Societies, 1983)
Fine, spiral, filamentous particles ~3 nm in diameter were consistently associated with hoja blanca-affected rice plants. The filamentous particles were isolated from infected plants following organic solvent clarification, concentration with polyethylene glycol, and equilibrium centrifugation in Cs2SO4 or CsCl gradients. Purified preparations exhibited typical nucleoprotein ultraviolet absorption spectra with a maximum at A260 nm and an A260/280 nm ratio of 1.4. The preparations contained one major and one minor protein of molecular weights 34 and 17.5 x 103 daltons, respectively, as determined by SDS-PAGE. In double immunodiffusion tests, an antiserum (prepared by injecting rabbits with purified preparations) produced specific precipitin reactions with leaf extracts of hoja blanca-affected rice plants, but not with leaf extracts of healthy rice plants. No serological reaction was observed in similar tests of leaf extracts from hoja blanca-infected Echinochloa colonum.